2003
DOI: 10.1103/physrevb.67.113401
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission spectroscopy of clean and potassium-intercalated carbon onions

Abstract: Hollow onionlike carbon ͑OLC͒, generated by annealing nanodiamond at 2140 K, has been studied by core-level and valence-band photoemission spectroscopy. Upon intercalation with potassium, core and valence states of the OLC show an almost rigid shift to higher binding energies, and the density of states at the Fermi level (E F ) is observed to increase. An asymmetric broadening of the C1s line from the OLC as intercalation proceeds indicates an increase in electron-hole pair excitations. Both core and valence-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
18
1
Order By: Relevance
“…37 A photoemission study of potassium intercalated polygonal hollow onions produced at 2140 K showed that these carbon onions behave as small graphite crystals and hence display bulklike rather than molecularlike behavior. 38 The x-ray emission study of OLC produced in the temperature range of 1600-1900 K revealed that their C K ␣ spectra exhibit a significant increase of the high-energy maximum and are markedly different from the spectrum of particles formed at 2140 K, which is very similar to the C K ␣ spectrum of polycrystalline graphite. 32 However, due to dipole selection rules, the x-ray emission spectra yield information on the partial density of states.…”
Section: Introductionmentioning
confidence: 55%
See 3 more Smart Citations
“…37 A photoemission study of potassium intercalated polygonal hollow onions produced at 2140 K showed that these carbon onions behave as small graphite crystals and hence display bulklike rather than molecularlike behavior. 38 The x-ray emission study of OLC produced in the temperature range of 1600-1900 K revealed that their C K ␣ spectra exhibit a significant increase of the high-energy maximum and are markedly different from the spectrum of particles formed at 2140 K, which is very similar to the C K ␣ spectrum of polycrystalline graphite. 32 However, due to dipole selection rules, the x-ray emission spectra yield information on the partial density of states.…”
Section: Introductionmentioning
confidence: 55%
“…The first peak, at 2.8± 0.1 eV, is related to bonding in graphite. 32,38,62 Progressive graphitization of the ND in samples annealed at 1420 and 1600 K, and the eventual vanishing of sp 3 carbon from the C1s photoemission spectra ͑Fig. 4͒ in the sample annealed at 1800 K results in increasing intensity and sharpness of the peak at 2.8± 0.1 eV in the valence band spectra.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…A typical AFM topographic image is shown in When produced directly by annealing ultra-dispersed nanodiamond, OLC samples show a clear π plasmon loss in the C1s core-level photoelectron spectra 6 [11,18], which is notably absent in the spectra shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%